The Effect of Gross Regional Domestic Product and Investment Value on Regional Taxes and Regional Levies in East Luwu Regency - Muhammad Reza; Nasrun Julyarman; Hasbiyanto Hasbiyanto (Economos : Jurnal Ekonomi dan Bisnis, 2026)
Regional Original Revenue (PAD) constitutes a critical indicator for evaluating the fiscal autonomy of local governments. The principal components of PAD, namely regional taxes and levies, are substantially influenced by prevailing economic conditions and investment activities within a given region. This study seeks to examine the extent to which Gross Regional Domestic Product (PDRB) and investment affect regional tax and levy revenues in East Luwu Regency. Employing a quantitative research design, the analysis utilizes secondary data sourced from the Central Statistics Agency and other relevant institutions over a defined observation period 2015-2024. Multiple linear regression is applied to assess both the partial and simultaneous effects of PDRB and investment on regional tax and levy revenues. The findings reveal that PDRB and investment exert a positive and statistically significant impact on regional tax revenues. Enhanced economic activity and increased investment inflows contribute to the expansion of the regional tax base through higher production levels, improved household income, and accelerated business growth. Meanwhile, PDRB and investment also have a positive effect on regional levies, but with a relatively weaker level of influence. This shows that regional levy revenue is not only determined by economic growth and investment, but is also greatly influenced by tariff policies, the quality of public services, and the effectiveness of levy management. Simultaneously, PDRB and investment have proven to play an important role in increasing regional fiscal capacity, especially through regional taxes as the main instrument of PAD. These findings provide policy implications that local governments need to encourage economic growth and create a conducive investment climate, as well as optimize the management of regional taxes and levies efficiently and sustainably